Consumer expectations, natural disasters, and stock market participation - Alexander M. Dietrich; John Leer; Raphael Schoenle (Danmarks Nationalbank, 2024)
We quantify consumers' expectations about natural disasters in an international survey. Consumers across several countries expect the likelihood of natural disasters to increase over the next few decades. What's more, national differences in disaster expectations correlate with the heterogenous risk exposure of individual countries. Finally, we show that for high-income consumers, higher subjective disaster expectations correlate with a lower likelihood of stock market participation. This may raise the demand for safe assets and potentially weigh on the natural rate of interest in the future.
Keywords: 330